Catalytic properties of the ferryl ion in the solid state: a computational review. Issue 10 (12th April 2022) - Saiz, Fernan; Bernasconi, Leonardo
Abstract : This review summarises the last findings in the emerging field of heterogeneous catalytic oxidation of light alkanes by ferryl species supported on solid-state systems such as the conversion of methane into methanol by FeO-MOF74. Abstract : The Fe(iv )O (ferryl) moiety plays a crucial role in a variety of biological processes involved in the production and storage of chemical energy, including aerobic respiration and catabolism. Its catalytic activity is crucially related to its anomalously high electrophilic character, which explains its ability to oxidise various substrates, including unreactive hydrocarbons. Attempts to reproduce this extraordinary oxidative ability in vitro have largely focused on relatively small Fe(iv )O complexes with a variety of coordinating ligands in various solvents (including water). Far less work has been devoted to solid-state Fe(iv )O systems capable of exhibiting reactivities comparable to biological and/or solvated systems. In this review, we address the chemical and catalytic properties of Fe(iv )O reactive groups supported by solid-state systems. We outline the electronic structure features explaining the Fe(iv )O reactivity in metal–organic frameworks and zeolites and we draw a comparison to the more extensive work carried out on biological and bio-mimetic systems.